THE PHENOMENON OF “IRRITATING” COLORS IN THE FIELD OF DESIGN - Ralko, Maria; Varchenko, Yuriy; Bulatov, Valery; Vasylenko, Angela (Theory and practice of design, 2023)
Color has an effect on most of the senses: sight, hearing, smell, taste, so the color decision in product design occupies an important place, and «annoying» colors can cause a number of negative feelings that will affect the perception of the color range. The subconscious influence of color gamut on the choice and emotional state of recipients during interaction with color solutions has also been established. The purpose of the article is to investigate the aspects of the phenomenon of colors, namely «annoying» colors in the field of design and the peculiarities of their application. Methodology. The research used the following methods of analysis: complex and systematic, generalization and comparison, with which the definition of the main questions of the research topic was determined, and to present further ways of modern use of knowledge about the influence of «irritating colors in the field of design». The results. The advantages of «annoying» colors in the field of design are substantiated and defined. The most popular and most effective associative meanings of colors, shades and color combinations, their influence on the formation of a person’s emotional state were analyzed: warm colors mostly evoke more pleasant feelings and emotions, but they also carry a warning of danger and a negative connotation; negative aspects prevail in cold colors, but they also have a positive and sometimes calming effect. The concept of color harmony and balance is considered. It shows how experienced designers can deliberately use «annoying» colors as attention- grabbing elements in a harmonious palette, creating visual interest. A comparative table was built for this color analysis and the influence of color on mood, accentuation, storyline and emotions conveyed by the advertising image through color combination was visually examined. The purpose with which representatives of various professions, not only related to design, use this phenomenon in their work or everyday life has been studied. Scientific novelty consists in the study of aspects of «annoying colors in the field of design and the peculiarities of their application. Practical significance. The analysis and processing of the information of the source base, the presented conclusions enriched the vision of this issue and served in determining the direction of the next study regarding the influence of «annoying» colors on the psychological state of a person in the field of design.